How round is a protein? Exploring protein structures for globularity using conformal mapping - Hass, Joel; Koehl, Patrice (Frontiers in Molecular Biosciences, 2014)
We present a new algorithm that automatically computes a measure of the geometric difference between the surface of a protein and a round sphere. The algorithm takes as input two triangulated genus zero surfaces representing the protein and the round sphere, respectively, and constructs a discrete conformal map between these surfaces. The conformal map is chosen to minimize a symmetric elastic energy that measures the distance of the constructed conformal map from an isometry. We illustrate our approach on a set of basic sample problems and then on a dataset of diverse protein structures. We show first that the symmetric elastic energy is able to quantify the roundness of the Platonic solids and that for these surfaces it replicates well traditional measures of roundness such as the sphericity. We then demonstrate that the symmetric elastic energy captures both global and local differences between two surfaces, showing that our method identifies the presence of protruding regions in protein structures and quantifies how these regions make the shape of a protein deviate from globularity. Based on these results, we show that the symmetric elastic energy serves as a probe of the limits of the application of conformal mappings to parametrize protein shapes. We identify limitations of the method and discuss its extension to achieving automatic registration of protein structures based on their surface geometry.